The seasonal nature of tourist flows in relation to meteorological conditions as illustrated by the case of Zachodniopomorskie Voivodeship - Koźmiński, Czesław; Michalska, Bożena (Bulletin of Geography. Socio-economic Series, 2016)
The analysis is based on the materials published by the Statistical Office in Szczecin for 2000-14, presented on a monthly basis, concerning the total number of tourists (including foreign tourists) and the overnight stays. The distribution of the number of tourists and their accommodation per month and season was correlated with mean monthly values for air temperature, cloudiness and wind speed. Meteorological data for the period 2000-14, as averaged for the whole voivodeship, was obtained from four IMGW stations (Świnoujście, Koszalin, Szczecin and Szczecinek). Statistical analysis was conducted and time trends of the number of tourists and overnight stays were identified for individual months with the use of linear and polynomial regression. The seasonal nature of tourist flows was assessed by the number of tourists and accommodation provided for tourists in summer compared to winter, and spring to autumn. Air temperature and cloudiness were found to have the greatest effect on the uneven distribution of tourist numbers across a year. Each year, approximately 1.7 million tourists visit Zachodniopomorskie Voivodeship, 1.1 million of which (i.e. 66%) stay on the coast.